Assessing the Usability of an Instagram Filter in Monitoring Essential Tremor: A Proof‐of‐Concept Study. Issue 2 (4th November 2022) - Ismail, Ismail Ibrahim; Kamel, Walaa A.; Al‐Hashel, Jasem Youssef
ABSTRACT: Background: Spiral drawing is an important test in monitoring essential tremor (ET). With the rise of telemedicine amid the coronavirus disease 2019 pandemic, a contactless tool for monitoring tremors was required. We aimed to assess the validity of a novel smartphone technology using a video‐based social media platform for rapid and objective monitoring of ET. Methods: A prospective pilot study evaluated patients with ET in 2 clinic visits. Videos of tremors were recorded using a publicly available Instagram filter and were visually compared with spirals drawn by the patients. The level of agreement among the raters was evaluated. Results: A total of 12 patients with ET were recruited. A consensus between both raters was achieved for 11 patients (91.6%) for both spirals and videos with good interrater agreement (κ value, 0.755 ± 0.332). Conclusion: This novel method was found to be valid and easy to use in measuring ET in real‐world settings. Further research in a larger cohort is needed to suggest its use as a home‐based or clinic‐based monitoring tool.